A toddler with an unusually severe polyarticular arthritis and a lung involvement: a case report - Pietro Basile; Giulia Gortani; Andrea Taddio; Serena Pastore; Federica Corona; Alessandra Tesser; Egidio Barbi; Alberto Tommasini (BMC, 2022)
Abstract Background COPA syndrome is a rare hereditary inflammatory disease caused by mutations in the gene encoding the coatomer protein subunit alpha, causing excessive production of type I interferon. This case is a reminder for the general paediatrician, highlighting the relevance of the association between arthritis and lung involvement in toddlers. Case presentation We report the case of a 2-year-old girl with intermittent limping and joint pain. Her family history was relevant for a Still disease with lung involvement in the mother. Physical examination showed moderate wrist swelling. Laboratory findings on admission showed an increase in inflammatory markers, positive rheumatoid factor, antibodies antinuclear antibody (ANA) and cyclic citrullinated peptide (anti-CCP). Wrists' ultrasound documented synovial thickening, and chest X-rays showed an unexpected severe interstitial pneumopathy. Genetic testing confirmed the diagnosis of a heterozygous mutation of the COPA gene in c.841C > T (p.R281W). Janus kinase treatment was started (baricitinib, 4 mg daily per os) with a remarkable improvement in limping and joint pain after two weeks. Conclusions In cases of recurrent arthritis with family history and multiple involvement organs, a genetic disorder should be suspected and genetic testing should be performed. Furthermore, this case suggests that therapy with jak inhibitors may be effective and safe in interferonopathies.